Identification and characterization of potentially pathogenic bacteria isolated from two beaches on the northern coast of Pernambuco - Santos, Alison Rodrigues dos (2021)
Pernambuco has a large availability of solar energy and high temperatures, and is well known for the natural beauty of its beaches, which are frequented for leisure activities, such as: walks, diving, swimming lessons and the performance of various sports. With this, the beaches end up becoming an environment of great circulation, contributing to the impact of ecosystems, in addition to this factor we can report the expansion of industries, livestock, agriculture, and urban centers. All these factors influence the rise in the rate of sand contamination, due to the disposal of inorganic waste on the beaches or that brought by seawater. Thus, the present study aimed to identify and characterize potentially pathogenic bacteria isolated on the beaches of Itamaracá and Olinda, on the northern coast of Pernambuco.The bacterial isolates were submitted to biochemical tests, gram test and catalase. At Olinda beach, the bacteria Escherichia coli, Staphylococcus spp, Staphylococcus aureus, Streptococcus spp and Vibrio cholerae were identified. At Itamaracá beach, Escherichia coli, Klesbsiella pneumonia, Staphylococcus spp, Staphylococcus aureus, Streptococcus spp, and Vibrio cholerae were identified. However, the microbiological analyses showed that there is a high level of contamination in the beach sand, especially in the dry sand where there is more contact with bathers. Therefore, a monitoring of the sand is necessary to guarantee a sanitary quality.